Pemberdayaan Masyarakat Desa Sukamakmur Kabupaten Jember Dalam Budidaya Lobster Air Tawar - Basuki Basuki; Nurul Dwi Novikarumsari; Indah Ibanah; Indri Fariroh (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Sukamakmur Village is a village located in Ajung District, Jember Regency with residents making a living as farmers and cultivating freshwater fish. The location of Sukamakmur Village is very prospective for freshwater fish cultivation because of its strategic location in getting water, and the type of fish being cultivated is catfish. In the last period, most of the people who cultivate catfish have gone out of business due to increasing feed prices while the selling value of catfish is unable to cover. The purpose of this community service program is to increase the standard of living and welfare of the people of Sukamakmur Village through the cultivation of freshwater crayfish as a substitute for catfish commodities. The method used for service program activities is through socialization, training, mentoring, and evaluation approaches. The results of the activity show that the community is enthusiastic in implementing freshwater crayfish cultivation because the cultivation method is very easy and requires low costs. Another result obtained is that the community can start new businesses, especially those that have gone out of business due to catfish cultivation so that they can bounce back in increasing their income